2016
DOI: 10.1162/jocn_a_01009
|View full text |Cite
|
Sign up to set email alerts
|

Decompositional Representation of Morphological Complexity: Multivariate fMRI Evidence from Italian

Abstract: Derivational morphology is a cross-linguistically dominant mechanism for word formation, combining existing words with derivational affixes to create new word forms. However, the neurocognitive mechanisms underlying the representation and processing of such forms remain unclear. Recent cross-linguistic neuroimaging research suggests that derived words are stored and accessed as whole forms, without engaging the left-hemisphere perisylvian network associated with combinatorial processing of syntactically and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…This interpretation of our brain imaging results are aligned with the predictions of the dualsystems framework described in the introduction (Marslen-Wilson et al, 2014;Tyler & Marslen-Wilson, 2008), where it's expected that inflectional morphology will rely on brain regions including the left IFG. Other studies, including ones that have been designed to probe this framework, have also observed more extensive activation of left BA44 with increasing combinatorial load where inflectional morphology was involved (Bozic et al, 2007(Bozic et al, , 2015Carota et al, 2016;Klimovich-Gray et al, 2017;Schell et al, 2017). The specificity of our findings to the anterior-ventral Cluster 3 of BA44 is consistent with recent brain imaging findings on variations in combinatorial load within one language (Schell et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This interpretation of our brain imaging results are aligned with the predictions of the dualsystems framework described in the introduction (Marslen-Wilson et al, 2014;Tyler & Marslen-Wilson, 2008), where it's expected that inflectional morphology will rely on brain regions including the left IFG. Other studies, including ones that have been designed to probe this framework, have also observed more extensive activation of left BA44 with increasing combinatorial load where inflectional morphology was involved (Bozic et al, 2007(Bozic et al, , 2015Carota et al, 2016;Klimovich-Gray et al, 2017;Schell et al, 2017). The specificity of our findings to the anterior-ventral Cluster 3 of BA44 is consistent with recent brain imaging findings on variations in combinatorial load within one language (Schell et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Inflectional morphology, which is computationally more complex, is expected to induce activation in the left hemisphere fronto-temporal regions (i.e., dorsal BA44 and pSTG), while derivational morphology is expected to engage bilateral temporal regions (i.e., STG and MTG; Klimovich-Gray, Bozic, & Marslen-Wilson, 2017). These predictions are borne out in studies having examined specific languages having different degrees of morpho-syntactic complexity, such as English, Arabic, Polish, Russian, and Italian (Boudelaa, Pulvermuller, Hauk, Shtyrov, & Marslen-Wilson, 2010;Bozic, Fonteneau, Su, & Marslen-Wilson, 2015;Bozic, Marslen-Wilson, Stamatakis, Davis, & Tyler, 2007;Carota, Bozic, & Marslen-Wilson, 2016;Klimovich-Gray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although the simple nouns used in this experiment were words without inflectional affixes, they were typically multisyllabic words with onset-embedded pseudostems (e.g., cutlet, turnip), which are likely to generate cohort competition during spoken language comprehension. Our results are consistent with studies showing that bilateral temporal areas are implicated in the accessing of semantic representations of words (Binder, Desai, Graves, & Conant, 2009;Jung-Beeman, 2005) as well as studies showing that bilateral IFG and temporal areas are engaged in processing perceptually complex words (e.g., Carota, Bozic, & Marslen-Wilson, 2016;Zhuang, Tyler, Randall, Stamatakis, & Marslen-Wilson, 2014;Bozic et al, 2010).…”
Section: Distribution Of Syntactic Complexity Effectssupporting
confidence: 92%
“…not bound to the visual or auditory sensory modalities) that can be accessed and therefore primed during comprehension; (ii) the representation is somewhat stable in order to generalize across lexical contexts. Furthermore, findings from fMRI link the processing of derived forms with activity in the left inferior frontal gyrus (LIFG) [57]-i.e. Broca's areawhich is traditionally associated with syntactic processing, broadly construed.…”
Section: (Ii) Derivation Accessmentioning
confidence: 99%